Comparative outcomes of manual compression, double-ProGlide and the LaPFOE technique following cryoballoon atrial fibrillation ablation with uninterrupted oral anticoagulants - Jiayin Sun; Ji Wu; Hailiang Yu; Debao Zhang; Hongya Han; Zhiming Zhou; Dean Jia; Dongmei Shi; Yujie Zhou; Shiwei Yang (BMC Cardiovascular Disorders)
Abstract Background Groin complications are considered to be the most common adverse events during cryoballon ablation. We aimed to compare the safety and cost-effectiveness of the LaPFOE technique (combined low approach femoral venous puncture, pre-dilation with a femoral artery sheath core, and figure-of-eight suture) with double-ProGlide technique and manual compression after cryoballoon ablation for atrial fibrillation with uninterrupted oral anticoagulants. Methods Conventional manual compression, the double-ProGlide technique and the LaPFOE technique were applied in the first 100 patients, the following 92 patients, and the last 100 patients, respectively. The occurrence of groin complications was evaluated immediately and at the three-month follow-up. Results A total of 292 participants (71.23% male, mean age 60.48 ± 9.71 years) were enrolled. Major vascular complications were not observed in both the ProGlide group and the LaPFOE group, while three occurred in the manual compression group. The incidence of any groin complication was significantly greater in patients who underwent manual compression than in their counterparts who underwent either the ProGlide or LaPFOE technique [18 (18.00%) vs. 3 (3.26%) vs. 0 (0.0%); P < 0.05]. Compared with the manual compression group, both the ProGlide group and the LaPFOE group achieved faster hemostasis, earlier patient ambulation and shorter total electrophysiology laboratory time and hospital stay after the procedure (P < 0.001). The highest hospital cost was observed in the ProGlide group, whereas the lowest was shown in the LaPFOE group [10.53 (10.28, 10.63) ×104 yuan vs. 9.73 (9.47, 10.05) ×104 yuan vs. 9.55 (9.43, 9.66) ×104yuan, P < 0.05]. Conclusions The LaPFOE technique is safe and cost-effective and has clinical benefits in lowering the occurrence of any groin complications, shortening the total electrophysiology laboratory time and hospital stay after the procedure and reducing hospital cost.